2019
DOI: 10.7759/cureus.4358
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Caregiver Stress in Relation to Severity of Disease in Persons with Parkinson’s

Abstract: Introduction Parkinson’s disease (PD) is a progressive neurological disorder. It presents with motor symptoms and gradually progresses to cognitive impairment. It has debilitating impact not only on the psychological health of the patient but also of the caregivers. The aim of this study is to evaluate the stress level among caregivers of PD and assess its correlation with the disease factors including duration, severity, and presence of on-off phenomenon. Methods One hundred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 13 publications
2
17
0
1
Order By: Relevance
“…A study reported that the severity of stress in caregivers was correlated with their gender. 31 Similar to this result, a study reported that PDCs had more anxiety and depressive symptoms than their male counterparts. 8 …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A study reported that the severity of stress in caregivers was correlated with their gender. 31 Similar to this result, a study reported that PDCs had more anxiety and depressive symptoms than their male counterparts. 8 …”
Section: Discussionsupporting
confidence: 71%
“…In line with our results, a recent study indicated that the stress level among PDCs was correlated with the duration and severity of PD in patients. 31 Another study reported that PDCs had more severe depression, greater tiredness, and less life satisfaction compared with the healthy elderly population. 32 …”
Section: Discussionmentioning
confidence: 99%
“…These patients were also less likely to live alone and more likely to be living in a nursing home and being cared for by a professional caregiver than those who had no "OFF" episodes. This suggests an increasing caregiver burden associated with "OFF" episodes, as was observed in other studies 26 . Effect associated with the hourly change in "OFF" time (i.e.…”
Section: Discussionsupporting
confidence: 82%
“…[39][40][41] Similar studies in PD are needed to examine longitudinal associations. For instance, the relationship between severity of PD and care partner burden has been examined cross-sectionally, 42 but not longitudinally. Factors of interest related to the person with PD that have not yet been evaluated in longitudinal literature in PD, but have been identified as potentially relevant in cross-sectional studies or longitudinally in other chronic neurological diseases are motor severity, disease-related symptoms (psychosis, cognitive impairment, apathy, impulse control disorders, etc.…”
Section: Discussionmentioning
confidence: 99%